Receptor-induced conformational changes in the subgroup A avian leukosis and sarcoma virus envelope glycoprotein. - Gilbert, J M (1995)
We recently reported that Tva, the host cell receptor for subgroup A avian leukosis and sarcoma viruses, binds specifically to the subgroup A envelope glycoprotein (Env-A) (J.M. Gilbert, P. Bates, H. E. Varmus, and J. M. White, J. Virol. 68:5623-5628, 1994). Here we have tested the hypothesis that binding of Tva causes conformational changes in Env-A that correlate with its conversion from a fusion-inactive to a fusion-active state. Conformational changes were examined by both a proteolysis and an immunoprecipitation assay. A temperature-dependent conformational change, demonstrated by the generation of a specific thermolysin digestion product of the surface (SU) subunit, occurred when a soluble form of Tva (sTva) was incubated with Env-A. sTva did not induce this conformational change in Env-C or in a noninfectious precursor form of Env-A, Env-A CL. However sTva did induce the conformational change in Env-A CL that had been pretreated in vitro to produce the SU and transmembrane (TM) subunits. Moreover, interaction of Tva with Env-A at 25 degrees C, but not at 4 degrees C, appeared to reveal a previously buried segment of the putative fusion peptide of Env-A. Our results suggest that binding of Tva to Env-A results in specific conformational changes in the Env-A glycoprotein that are relevant to the activation of its fusion function.